Analysis of intracellular tyrosine phosphorylation in circulating neutrophils as a rapid assay for the in vivo effect of oral tyrosine kinase inhibitors - Futosi, Krisztina; Bajza, Boglárka; Deli, Dorottya; Erdélyi, András; Tusnády, Simon; Mócsai, Attila (Frontiers in Pharmacology, 2023)
Tyrosine kinases are crucial signaling components of various biological processes and are major therapeutic targets in various malignancies and immune-mediated disorders. A critical step of development of novel tyrosine kinase inhibitors is the transition from the confirmation of the in vitro effects of drug candidates to the analysis of their in vivo efficacy. To facilitate this transition, we have developed a rapid in vivo assay for the analysis of the effect of oral tyrosine kinase inhibitors on basal tyrosine phosphorylation of circulating mouse neutrophils. The assay uses a single drop of peripheral blood without sacrificing the mice. Flow cytometry using fluorescent intracellular staining by anti-phosphotyrosine antibodies revealed robust basal tyrosine phosphorylation in resting circulating neutrophils. This signal was abrogated by the use of isotype control antibodies or by pre-saturation of anti-phosphotyrosine antibodies with soluble phosphotyrosine amino acids or tyrosine-phosphorylated peptides. Basal tyrosine phosphorylation was dramatically reduced in neutrophils of triple knockout mice lacking the Src-family tyrosine kinases Hck, Fgr and Lyn. Neutrophil tyrosine phosphorylation was also abrogated by oral administration of the Abl/Src-family inhibitor dasatinib, a clinically used anti-leukemic agent. Detailed dose-response and kinetic studies revealed half-maximal reduction of neutrophil tyrosine phosphorylation by 2.9 mg/kg dasatinib, with maximal reduction observed 2 hours after inhibitor administration. Taken together, our assay allows highly efficient analysis of the in vivo effect of orally administered tyrosine kinase inhibitors, and may be used as a suitable alternative to other existing approaches.